Muslim mothers’ experiences in taking care of children with open heart surgery: A qualitative study in Southern Thailand - Lohmae, Userow; Pattanasombutsook, Maneeratsami; Chantarasiripoot, Boonkanas; Chemama, Nursaheeda; Thepsao, Saowapa; Maramoh, Rusna (Belitung Nursing Journal, 2025)
Background: A child with congenital heart disease requires complex surgeries and intensive postoperative care, causing significant stress for caregivers. Muslim caregivers, in particular, rely on their faith for strength. Objective: To explore the experiences of Muslim mothers caring for children who have undergone open heart surgery due to congenital heart disease. Methods: The study used a qualitative descriptive design conducted between February and June 2023. Data were collected through in-depth interviews with 12 Muslim mothers selected through purposive sampling, and thematic analysis was employed for data analysis. Results: Three main themes identified: 1) Strengthening faith and trust in God, which includes two subthemes—embracing acceptance amidst divine attribution and utilizing faith and belief as a wellspring of spiritual shelter, 2) Cultivating patience and resilience in life, encompassing two subthemes—endurance in caring with unconditional love and fostering resilience for coping strategies, and 3) The significance of social support systems, consisting two subthemes—healthcare professionals’ support and family support. Conclusions: This study revealed the complex emotional experiences, including sadness, loss, uncertainty, and resilience, of Muslim mothers whose children face open heart surgery and highlighted the vital role of holistic support from healthcare professionals and families. Recommendations in line with holistic nursing principles include providing comprehensive information, faith-based psychological support, and involving the family’s caregiving capacity. The study also calls for further research within the holistic nursing context, including programs to enhance psychosocial support in similar situations.